Financial flexibility across the euro area and the UK - Annalisa Ferrando; Maria-Teresa Marchica; Roberto Mura (European Central Bank (ECB), 2014)
We use a large database of more than 685,000 European firms to show that financial flexibility attained through conservative leverage policies is more important for private, small, medium-sized and young firms and for firms in countries with lower access to credit and weaker investor protection. Further, using the recent financial crisis as a natural experiment, we show that financial flexibility status allows companies to reduce the negative impact of liquidity shocks on their investment decisions. Our findings support the hypothesis that financial flexibility relates to companies' ability to undertake future investment, despite market frictions hampering possible profitable growth opportunities.
Keywords: G31; G32; D92; 330; cross-country analysis; financial flexibility; investment; low leverage